Pendidikan Kepanduan sebagai Wahana Pembentukan Disiplin Peserta Didik Sekolah Menengah Pertama di Era Digital - Ni Wayan Eka Yanti; I Wayan Lasmawan; I Nengah Suastika; I Made Pageh (Universitas Hamzanwadi, 2026)
This study aims to describe and analyze the role of Scout extracurricular activities in fostering and strengthening students’ disciplinary character in the school environment. The research employs a qualitative method with a descriptive approach to gain a comprehensive and in-depth understanding of how character development is implemented through Scout activities. The research subjects were selected using purposive sampling, involving nine informants consisting of the principal (1 person), vice principal for student affairs (1 person), Scout instructors (2 people), and students (5 people). This study was conducted over six months, from June 2025 to December 2025. Data were collected through observation, in-depth interviews, and documentation to ensure the validity and richness of the findings. The data analysis process was carried out systematically through stages of data reduction, data display, and conclusion drawing. The findings reveal that Scout's extracurricular activities play a significant and effective role in shaping students’ disciplinary character. This is achieved through direct habituation processes (learning by doing), consistent role modeling by instructors, and the implementation of the patrol system, which emphasizes responsibility, cooperation, and leadership. Furthermore, structured and routine activities such as regular training sessions, flag ceremonies, and camping programs contribute to strengthening the internalization of discipline-related values. These activities positively impact students’ behavior, as reflected in improved punctuality, rule compliance, responsibility, teamwork, and a heightened awareness of discipline in their daily school life.